КОГНІТИВНО-ОНОМАСІОЛОГІЧНИЙ АНАЛІЗ ОКАЗІОНАЛЬНОСТІ В АНГЛІЙСЬКІЙ МОВІ - ЦОНИНЕЦЬ, Марія (Науковий вісник Ужгородського університету. Серія Філологія, 2022)
In the article the cognitive and onomasiological analyses of occasionality in English are implemented. The topicality of the research lies in the cognitive features of the emergence of individual authors’ neologisms, including “inten- tional speech and mental activity. The purpose of the article is to determine the processes of forming an occasional unit as a consequence of cognitive and mental activities of human mind. The objectives of the study include: the definition of the term concept, clarifying the structure of the occasional unit, considering cognitive and onomasiological analyses of the author’s innovation developing and stages of their generation in terms of cognitive onomasiology. Language and thinking are special and highly complex phenomena, a result of language and speech interaction. This is, first of all, a counteraction of two ten- dencies – the development of language and its preservation. To represent, reproduce and fix new ideas and concepts, language has to be replenished with new components. Occasionalisms play an important role in the language system, formed mainly for the purpose of artistic and stylistic nomination operating within a certain context. Cognitive and onomasiological analyses consider nonce-words in the process of conception, that makes it possible to dive into their mental depth. It is meant that the person who created a new word has an individual lexicon, which is the conceptual basis of any nomination in speech. A person chooses a certain unit of nomination depending on the extent to which his/her semantics satisfies the conceptualization that is being verbalized. Cognitive determinants for the emergence of neologism are associated primarily with the receipt, processing, storage and transmission of information. This approach enables revealing the cognitive factors that contribute the formation of occasionalisms. In this case, we proceed from the recognition of the role of a human being as the creator of the communication process and, ultimately, as the main subjective factor that determines the main trends in the language system. Thus, cognitive and onomasiological analyses are combined, as they involve the identification of motivational bases during the nomination and aims to establish the relationship between the name and the denoted object and contributes to a better understanding of occasionalisms.